Initiative «One Belt, One Road» and current areas of investment cooperation between Kazakhstan and China - Ж.Е. Aшиновa; Сяоли, Цзинь (Journal of Oriental Studies, 2019)
China’s «One Belt, One Road» International Initiative is a completely new global mechanism for international cooperation, which aims at mutual benefit and successful development. The participating countries that are actively involved in it are gaining and will reap significant benefits, which is about 150 countries and more than 30 international organizations that have already signed cooperation documents with China in the framework of this initiative. The proposed article discusses the idea of creation and the main essence, content and implementation of the «One Belt, One Road» concept, issues of cooperation between China and Kazakhstan in the framework of the initiative under consideration. In order to reveal the current areas of investment cooperation between the countries, special attention was paid to the results of the KazakhChinese business forum dedicated to the 5th anniversary of the One Belt, One Road Initiative, which was held in 2018 in Astana. In conclusion, regarding the prospects of Kazakhstan from participating in this initiative, the authors concluded that Kazakhstan greatly benefits due to its favorable geographical location, since it is located in the center of the land part of the New Silk Road, as a result of which favorable opportunities are created for engaging in trade and infrastructure development industry. Key words: initiative “One BeltOne Way”, New Silk Road, Sea Silk Road, Kazakhstan, areas of cooperation, investments, forum.